A targeted sequence capture array for phylogenetics and population genomics in the Salicaceae. (25th October 2020) - Sanderson, Brian J.; DiFazio, Stephen P.; Cronk, Quentin C. B.; Ma, Tao; Olson, Matthew S.
Abstract : Premise: The family Salicaceae has proved taxonomically challenging, especially in the genus Salix, which is speciose and features frequent hybridization and polyploidy. Past efforts to reconstruct the phylogeny with molecular barcodes have failed to resolve the species relationships of many sections of the genus. Methods: We used the wealth of sequence data in the family to design sequence capture probes to target regions of 300–1200 bp of exonic regions of 972 genes. Results: We recovered sequence data for nearly all of the targeted genes in three species of Populus and three species of Salix . We present a species tree, discuss concordance among gene trees, and present population genomic summary statistics for these loci. Conclusions: Our sequence capture array has extremely high capture efficiency within the genera Populus and Salix, resulting in abundant phylogenetic information. Additionally, these loci show promise for population genomic studies.